Germ granule-mediated mRNA storage and translational control - Hoang-Anh Pham-Bui; Mihye Lee (RNA Biology)
Germ cells depend on specialized post-transcriptional regulation for proper development and function, much of which is mediated by dynamic RNA granules. These membrane-less organelles form through the condensation of RNA and proteins, governed by multivalent biomolecular interactions. RNA granules compartmentalize cellular components, selectively enriching specific factors and modulating biochemical reactions. Over recent decades, various types of RNA granules have been identified in germ cells across species, with extensive studies uncovering their molecular roles and developmental significance. This review explores the mRNA regulatory mechanisms mediated by RNA granules in germ cells. We discuss the distinct spatial organization of specific granule components and the variations in material states of germ granules, which contribute to the regulation of mRNA storage and translation. Additionally, we highlight emerging research on how changes in these material states, during developmental stages, reflect the dynamic nature of germ granules and their critical role in development.